2019
DOI: 10.5606/ehc.2019.66429
|View full text |Cite
|
Sign up to set email alerts
|

The long-term results of cemented Oxford unicompartmental knee arthroplasty: A single-center experience

Abstract: ÖZ Amaç: Bu çalışmada çimentolu Oxford medial unikompartmental diz artroplastisi (UDA)'nin uzun dönem klinik sonuçları, komplikasyonları ve sağkalım oranları araştırıldı ve bulgular UDA ve total diz artroplastisi (TDA)'nin literatürde bildirilen sonuçları ile karşılaştırıldı. Hastalar ve yöntemler: Çalışmada Mayıs 2007-Ağustos 2013 tarihleri arasında Oxford medial UDA uygulanan 115 hastanın (16 erkek, 99 kadın; ort. yaş 65.5±8.3 yıl; dağılım, 50-88 yıl) 133 dizi ortalama 126 ay takip edildi. Protez komplikasyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…even state that “we do not recommend the use of Oxford UKA surgery commonly in the treatment of medial compartment osteoarthritis” (page 239) and Schroer et al . that “The unacceptable rate of failure with the Oxford knee implant has led the principal investigator to discontinue its use in practice” (page 3538) 16, 17 . In the present study, we also found that the revision rate of the UKA group was higher than that of the OWHTO group, even though the two groups had similar outcomes and function recovery, and UKA showed a potential superiority in ERAS.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…even state that “we do not recommend the use of Oxford UKA surgery commonly in the treatment of medial compartment osteoarthritis” (page 239) and Schroer et al . that “The unacceptable rate of failure with the Oxford knee implant has led the principal investigator to discontinue its use in practice” (page 3538) 16, 17 . In the present study, we also found that the revision rate of the UKA group was higher than that of the OWHTO group, even though the two groups had similar outcomes and function recovery, and UKA showed a potential superiority in ERAS.…”
Section: Discussionsupporting
confidence: 55%
“…However, the outcomes of UKA vary in different reports. Crawford's report found that activity level does not affect survivorship of unicondylar knee arthroplasty, 15 while Sever's report showed that UKA had higher early‐stage aseptic revision rates than TKA 16 . Furthermore, in Schroer's research, UKA is deemed a complete failure due to the unacceptably high revision rate, which led the author to refuse to use it anymore 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the demands to improve life and health conditions of patients with osteoarthritis (OA), minimally invasive surgeries have been favorable to obtain satisfactory results when performing knee arthroplasty. [ 1 ] Rapid recovery surgical protocols are evidence-based multidisciplinary approaches targeted on multimodal patient care and primarily focused on enhancing functional recovery of patients. These protocols include patient education to cope with anxiety and stress of surgery, nutritional planning and avoidance of long hours of fasting, preemptive analgesia, avoidance of tourniquet use, rational antibiotic prophylaxis, local infiltration anesthesia, and early physical therapy modalities.…”
Section: Introductionmentioning
confidence: 99%
“…
There is an ongoing debate on whether unicompartmental knee arthroplasty (UKA) or total knee arthroplasty (TKA) for end-stage medial osteoarthritis (OA) provides better functional outcomes. [1] The main findings of a recent meta-analysis showed a shorter survival time for UKA, but better clinical and functional performance scores, compared to TKA. [2] However, other reviews have reported no statistically significant difference in the postoperative knee scores.
…”
mentioning
confidence: 99%